Critical Materials Present Danger to U.S. Manufacturing - Silberglitt, Richard (RAND Corporation, 2013)
A high percentage of many raw and semi-finished materials critical to U.S. manufacturing are imported. China is the controlling producer of 11 of these materials and has instituted export restrictions that have led to two-tier pricing, creating pressure to move manufacturing to China. This report suggests the need for actions to mitigate the impact of such market distortions on the global manufacturing sector.